Adult Life Satisfaction and the Role of Forgiveness After Childhood Sexual Abuse: Evidence from a Seventh-day Adventist Cohort - Morton, Kelly R. (Journal for the scientific study of religion, 2019)
Negative physical and mental health outcomes are well documented for those who experience child sexual abuse. We explore the role of three types of dispositional forgiveness (of self, of others, and by God) as effect modifiers of the child sexual abuse and life satisfaction relationship. In 2010-2011, a sample of 5,506 Seventh-day Adventists reported levels of forgiveness, life satisfaction, and whether or not they had experienced sexual abuse in each of the two age periods (younger than 8 years and 8-18 years). Reported experience of childhood sexual abuse lowered life satisfaction regardless of when the child sexual abuse occurred. Forgiveness of self and of others were associated with higher life satisfaction regardless of sexual abuse exposure. Feeling forgiven by God was associated with increased life satisfaction indirectly through forgiveness of self and others. However, for those abused later in childhood, the association of abuse with reduced life satisfaction was weaker for those who felt forgiven by God. These findings suggest forgiveness by God operates primarily through forgiveness of self (and others) but can also buffer the effects of childhood sexual abuse on later life satisfaction when the abuse occurs in childhood/adolescence.